Prognostic Factors of Peritoneal Metastases from Colorectal Cancer following Cytoreductive Surgery and Perioperative Chemotherapy - Yutaka Yonemura; Emel Canbay; Haruaki Ishibashi (The Scientific World Journal)
Background. Prolonged survival of patients affected by peritoneal metastasis (PM) of colorectal origin treated with complete cytoreduction followed by intraoperative hyperthermic intraperitoneal chemotherapy (HIPEC) has been reported. However, two-thirds of the patients after complete cytoreduction and perioperative chemotherapy (POC) develop recurrence. This study is to analyze the prognostic factors of PM from colorectal cancer following the treatment with cytoreductive surgery (CRS) + POC. Patients and Methods. During the last 8 years, 142 patients with PM of colorectal origin have been treated with CRS and perioperative chemotherapy. The surgical resections consisted of a combination of peritonectomy procedures. Results. Complete cytoreduction (CCR-0) was achieved at a higher rate in patients with peritoneal cancer index (PCI) score less than 10 (94.7%, 71/75) than those of PCI score above 11 (40.2%, 37/67). Regarding the PCI of small bowel (SB-PCI), 89 of 94 (91.5%) patients with ≤2 and 22 of 48 (45.8%) patients with SB-PCI ≥ 3 received CCR-0 resection (P<0.001). Postoperative Grade 3 and Grade 4 complications occurred in 11 (7.7%) and 14 (9.9%). The overall operative mortality rate was 0.7% (1/142). Cox hazard model showed that CCR-0, SB-PCI ≤ 2, differentiated carcinoma, and PCI ≤ 10 were the independent favorite prognostic factors. Conclusions. Complete cytoreduction, PCI, SB-PCI threshold, and histologic type were the independent prognostic factors.